(854) Analytical Study for Expenditure on Food in the Private Sector - Mahmoud, M. W (Institute of National Planning, 2026)
Abstract This research represents a distinguished quantitative contribution to the analysis of household food consumption expenditure patterns. The study departs from a foundational empirical observation that food constitutes the single most significant category of individual expenditure in the U.A.R., accounting for approximately 55% of personal income, with average per capita food expenditure rising from 1,016 grams in 1951/52 to 1,261 grams in 1963/64. The authors employ an advanced statistical methodology to establish functional relationships between average expenditure on distinct food commodity groups (z) and total annual per capita expenditure (x), concluding that the quadratic function z = ax² + bx + c provides the best fit for most food categories, while the inverse linear function 1/z = a + b/x best represents cereals and starches and dry beans. The food groups analyzed encompass cereals and starches, dry beans, meat, fish and eggs, oils and fats, milk and milk products, vegetables, fruits, sugar and sugar products, and other foodstuffs. Expenditure elasticity coefficients (E) were computed for each commodity group separately for urban and rural regions, revealing significant differentials: fruit elasticity reached 1.30 in urban and 1.53 in rural areas, meat, fish and eggs registered 1.007 and 1.09 respectively, while cereals and starches recorded the lowest elasticities of 0.18 and 0.52, reflecting their status as necessities with early saturation at rising income levels. The paper includes a rigorous mathematical appendix detailing linear and quadratic regression procedures using the method of least squares, supplemented by two FORTRAN computer programs for estimating regression coefficients and testing their statistical significance, representing a pioneering application of computational methods in Egyptian economic research of the era. تُمثّل هذه الورقة البحثية إسهاماً أكاديمياً متميزاً في مجال الاقتصاد الكمي وتحليل أنماط الإنفاق الاستهلاكي على الغذاء. وقد انطلقت الدراسة من حقيقة إحصائية جوهرية مفادها أن الغذاء يُشكّل أهم بنود الإنفاق الفردي في جمهورية مصر العربية، إذ يستأثر بنحو 55% من الدخل الفردي، فضلاً عن ارتفاع متوسط الإنفاق الغذائي للفرد من 1016 غراماً في عام 1951/52 إلى 1261 غراماً في عام 1963/64. واعتمد الباحثان منهجاً إحصائياً متقدماً يقوم على تحديد العلاقة الدالية بين متوسط الإنفاق على مجموعات الغذاء المختلفة (z) وإجمالي الإنفاق السنوي للفرد (x)، حيث خلصا إلى أن الدالة التربيعية z = ax² + bx + c هي الأنسب لتمثيل معظم المجموعات الغذائية، في حين وجدا أن الدالة الخطية المعكوسة 1/z = a + b/x تُلائم الحبوب والنشويات والفول الجاف. وقد شملت المجموعات الغذائية المدروسة: الحبوب والنشويات، والفول الجاف، واللحوم والأسماك والبيض، والزيوت والدهون، والألبان ومنتجاتها، والخضروات، والفاكهة، والسكر ومنتجاته، وسائر المواد الغذائية. كما احتسب الباحثان معاملات مرونة الإنفاق (E) لكل مجموعة وفق البيئتين الحضرية والريفية، وكشفت النتائج عن تباينات دالة بين القطاعين؛ إذ بلغت مرونة الفاكهة 1.30 حضرياً و1.53 ريفياً، ومرونة اللحوم والأسماك والبيض 1.007 حضرياً و1.09 ريفياً، في حين انخفضت مرونة الحبوب والنشويات إلى 0.18 و0.52 على التوالي، مما يعكس طابعها الضروري وإشباعها المبكر مع تزايد الدخل. وتضمّنت الدراسة ملحقاً رياضياً وافياً يعرض أساليب الانحدار الخطي والتربيعي وطريقة المربعات الصغرى، إلى جانب برنامجين حاسوبيين بلغة فورتران لتقدير معاملات الانحدار والتحقق من دلالتها الإحصائية.